How do you simplify the expression #[(b^9)^-1]^-2# using the properties?

1 Answer
Mar 30, 2017

Answer:

See the entire simplification process below:

Explanation:

Use this rule of exponents to first simplify the bracketed term and then to simplify the term within the parenthesis:

#(x^color(red)(a))^color(blue)(b) = x^(color(red)(a) xx color(blue)(b))#

#[(b^9)^color(red)(-1))]^color(blue)(-2) = (b^9)^(color(red)(-1) xx color(blue)(-2)) = (b^9)^2#

#(b^color(red)(9))^color(blue)(2) = b^(color(red)(9) xx color(blue)(2)) = b^18#